2007
DOI: 10.1097/01.inf.0000247108.86199.64
|View full text |Cite
|
Sign up to set email alerts
|

Mycetoma in Children: Experience With 15 Cases

Abstract: Mycetomas are exceptional in children; in our setting, actinomycetomas are more frequent than eumycetomas. The clinical and microbiologic diagnosis is simple. Overall, treatment response is better for actinomycetomas than for eumycetomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…Some cases were reported in elderly, however we must consider that the infection may have started many years ago, suggesting that these individuals may have acquired the disease in youth. Moreover, only 4% of the cases were reported in patients <18 years old similar to previously reported studies [6], [30]. The percentage of children infected in our study (and other reports [6], [30]) differed from a report by Fahal et al [31] that described a 15% infection rate (n = 722) in children in Sudan, this was probably due to their outdoor work activities.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Some cases were reported in elderly, however we must consider that the infection may have started many years ago, suggesting that these individuals may have acquired the disease in youth. Moreover, only 4% of the cases were reported in patients <18 years old similar to previously reported studies [6], [30]. The percentage of children infected in our study (and other reports [6], [30]) differed from a report by Fahal et al [31] that described a 15% infection rate (n = 722) in children in Sudan, this was probably due to their outdoor work activities.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, only 4% of the cases were reported in patients <18 years old similar to previously reported studies [6], [30]. The percentage of children infected in our study (and other reports [6], [30]) differed from a report by Fahal et al [31] that described a 15% infection rate (n = 722) in children in Sudan, this was probably due to their outdoor work activities. However, the same study reported trauma in only 22.5% patients suggesting that different mechanisms of infection that deserve to be clarified [1], [31].…”
Section: Discussionsupporting
confidence: 72%
“…A hormonal cause could explain the greater susceptibility of men. This hypothesis is supported by the fact that eumycetoma growth is inhibited in the presence of progesterone [2,19,20], by the observation that in case of pregnancy mycetomas are more active [16], and that on the contrary in children they are less frequent and less aggressive [6,21].…”
Section: Clinical and Diagnostic Aspectsmentioning
confidence: 81%
“…In children the disease is uncommon and foot is commonly involved site. In a retrospective study spanning 25 years, out of 334 mycetomas, only 2 cases of eumycetoma were encountered in children of 15 years or younger (0.6), only 4.5% patients out of 334 [3] were in this age group and foot was affected in 66.6% of them. Both the eumycetomas in this study were caused by Madurella mycetomats.…”
Section: Discussionmentioning
confidence: 99%